PERAN BANK INDONESIA DALAM MENANGGULANGI TINDAK PIDANA MONEY LAUNDERING - Setiyanto, Budi (Yustisia, 2012)
AbstractThe aim of the study is to understand the role and constraints of Bank Indonesia in eradicating the crime of money laundering. This research included in empirical legal research is a descriptive qualitative. Location of research at Bank Indonesia Solo. The data used are primary and secondary data,  data collections  by interview and literature study, analysis of data using qualitative analysis. Based on the results of this research is that Bank Indonesia in order to participate as well as eradicating crime of money laundering and has issued a Circular Letter of Bank Indonesia. In the implementation of supervision and oversight of the implementation of Programme Implementation of Anti-Money Laundering (Money Laundering), Bank Indonesi requires each commercial bank to report the results of the Application of Anti-Money Laundering Program Compliance to the Chair through the Director of Public Bank. Head of Commercial Bank submitted the report to the Head Office of Bank Supervision of Bank Indonesia Solo through the Young Senior, having studied and revised and then submitted to the Head of Bank Indonesia Central Jakarta. In the implementation of the Application of Anti-Money Laundering Program, Office of Bank Indonesia Solo, many having some problems so it can not work optimally.